Curating the fieldwork playlist. - Fenby-Hulse, Kieran (2018)
In this essay, I consider the music that has been chosen as part of the previous essays in this collection. I attempt to understand what this assemblage of musical tracks, this anthropology playlist, might tell us about fieldwork as a research practice. The chapter examines this history of the digital playlist before going on to analyse the varied musical contributions from curatorial, musicological, and anthropological perspetives. I argue that the playlist asks us to reflect on the field of anthropology and to consider the role of the voice, the body, the mind with anthropology, as well as the role digital technologies, ethics, and the relationship between indviduals and the community.
jufo:1
Peri2020 ; B
Keywords: kenttätyö; antropologit; musiikki; laulut; soittolistat; kulttuuriantropologia; fältarbete; antropologer; musik; sånger; spellistor (musik); kulturantropologi